Kahneman, Daniel : Thinking, Fast and Slow - Kahneman, Daniel (Great Britain Penguin Books, 2012)
It is an astonishingly rich book: lucid, profound, full of intellectual surprises and self-help value. It is consistently entertaining and frequently touching, especially when Kahneman is recounting his collaboration with Tversky . . . So impressive is its vision of flawed human reason that the New York Times columnist David Brooks recently declared that Kahneman and Tversky's work 'will be remembered hundreds of years from now,' and that it is 'a crucial pivot point in the way we see ourselves.' They are, Brooks said, 'like the Lewis and Clark of the mind' . . . By the time I got to the end of Thinking, Fast and Slow, my skeptical frown had long since given way to a grin of intellectual satisfaction. Appraising the book by the peak-end rule, I overconfidently urge everyone to buy and read it. But for those who are merely interested in Kahenman's takeaway on the Malcolm Gladwell question it is this: If you've had 10,000 hours of training in a predictable, rapid-feedback environment-chess, firefighting, anesthesiology-then blink. In all other cases, think
Keywords: Psycology; Best seller